An Analysis of the Sensitivity of the Activated Partial Thromboplastin Time (APTT) Assay, as Used in a Large Laboratory Network, to Coagulation Factor Deficiencies. Issue 1 (12th February 2022) - Do, Louis; Favaloro, Emmanuel; Pasalic, Leonardo
Abstract: Objectives: To advance knowledge in using the ex vivo method to identify factor sensitivity of the activated partial thromboplastin time (APTT), using data from a hemophilia and reference hemostasis laboratory; to evaluate application of inclusion and exclusion criteria to eliminate data outliers; and to discuss outcomes with reference to comparable studies. Methods: An ex vivo, retrospective analysis was performed on patient samples with conjointly ordered APTT and intrinsic pathway factors (VIII, IX, XI, XII) for application to a large network of laboratories. The relationship between factor levels and APTT, before and after application of exclusion criteria, is demonstrated. Results: Curvilinear relationships were found between all factor levels and APTTs, which demonstrated both similarities and differences with available studies. Factor sensitivity data are presented. Study strengths include large sample size and use of real-world data. Limitations include inability to exclude all residual outliers and paucity of patient samples singularly deficient in factors other than FVIII. Conclusions: This ex vivo, retrospective analysis of the sensitivity of the APTT assay to intrinsic pathway factor deficiencies using real-world data from a hemophilia and reference hemostasis laboratory contains the largest sample size using this approach to date. The outcomes assist in informing practice in this area and can be used as a reference for further studies.